Promoting RRI and active citizenship in an inquiry-based controversial socio-scientific issue: the case of cholesterol regulation with statins - Hadjichambis, Andreas Ch.; Georgiou, Yiannis; Paraskeva-Hadjichambi, Demetra; Kyza, Eleni A.; Agesilaou, Andria; Mappouras, Demetrios G. (My University, 2019)
Science education is an important dimension of the European Commission’s Responsible Research and Innovation (RRI) objectives; however, RRI is not an explicit focus of biology teaching and few biology teachers have experience in integrating RRI in classroom practice. This study examines the impact of a three 80-minute RRI and active citizenship module on 11th grade biology students, based on the SSIBL pedagogical framework. A representative national sample of 11th grade biology students in Cyprus (n = 398) participated. A pre-post research design examined impact in relation to students’ conceptual understanding regarding cholesterol and its regulation, their understanding of the controversy about cholesterol regulation, awareness of RRI components, feeling of responsibility and willingness to act. Analyses indicated statistically significant gains in conceptual understanding and the understanding of the controversy about cholesterol regulation and awareness of RRI components, as well as in students’ socio-scientific accountability (feeling of responsibility and willingness to act). Conceptual understanding showed increased correlations with Controversy understanding and RRI understanding forming the three of them the cognitive elements of individuals understanding. All of the examined variables are deemed, as of great importance for the design, implementation and evaluation of innovative biology RRI and active citizenship modules.
Keywords: Active citizenship; Biology education; Conceptual understanding; Controversial socio-scientific issues; Inquiry-based learning; Responsible Research and Innovation (RRI)